A functional polymorphism in the promoter of miR-17-92 cluster is associated with decreased risk of ischemic stroke - Huatuo Huang; Guijiang Wei; Chunfang Wang; Yulan Lu; Chunhong Liu; Rong Wang; Xiang Shi; Jun Yang; Yesheng Wei (BMC, 2019)
Abstract Background The microRNA-17-92 (miR-17-92) cluster is one of the most extensively studied miRNA clusters. Abnormal expression of the cluster has been found to play important role in different kinds of human diseases, including ischemic stroke (IS). The aim of our study was to investigate the association between three polymorphisms (rs1491034, rs9301654 and rs982873) in the promoter of the miR-17-92 cluster and risk of IS. Methods Three hundred and ninety-eight patients with IS and 397 control subjects were included. The genotypes of the three polymorphisms were determined by Snapshot SNP genotyping assay. Relative expression of the cluster in peripheral blood mononuclear cells (PBMCs) of cases and controls were examined by quantitative real-time PCR. Results Significant association between rs9301654 polymorphism and risk of IS were observed basing on genotype, model and allele analyses (GA vs. AA: adjusted OR = 0.63, 95% CI: 0.41~0.97, P = 0.037; GG vs. AA: adjusted OR = 0.23, 95% CI: 0.07~0.78, P = 0.018; GA + GG vs. AA: adjusted OR = 0.57, 95% CI: 0.38~0.87, P = 0.009; GA + AA vs. GG: adjusted OR = 0.27, 95% CI: 0.08~0.89, P = 0.032; G vs. A: adjusted OR = 0.58, 95% CI: 0.40~0.83). Haplotype analysis showed that TGC and TGT haplotypes were associated with decreased risk of IS (OR = 0.59, 95% CI: 0.40~0.87, P = 0.007 for TGC haplotype; OR = 0.21, 95% CI: 0.06~0.75, P = 0.009 for TGT haplotype). Importantly, we found the expression of miR-17-5p was significant higher while miR-19a-3p was significant lower in patient with IS compared with the control group (P < 0.01), and patients with rs9301654GG or GA genotype displayed lower level of miR-19a-3p compared with the AA genotype (P < 0.01). Conclusions Our findings indicated that rs9301654 polymorphism in the promoter of miR-17-92 cluster may be associated with susceptibility of IS in the Chinese population. However, we found that rs9301654 polymorphism and its respective gene expression did not demonstrate consistent association with IS in the Chinese population. Further studies such as gene-gene interaction are warranted to reveal the role of miR-19a and its regulatory genes in the etiology of IS.